2012
DOI: 10.3389/fonc.2012.00162
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine pathway inhibition as a novel therapeutic approach to treating neuroblastoma

Abstract: Polyamines are highly regulated essential cations that are elevated in rapidly proliferating tissues, including diverse cancers. Expression analyses in neuroblastomas suggest that up-regulation of polyamine pro-synthetic enzymes and down-regulation of catabolic enzymes is associated with poor prognosis. Polyamine sufficiency may be required for MYCN oncogenicity in MYCN amplified neuroblastoma, and targeting polyamine homeostasis may therefore provide an attractive therapeutic approach. ODC1, an oncogenic MYCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 101 publications
2
60
0
Order By: Relevance
“…These metabolic differences are modulated by the different molecular phenotypes frequently observed in cancer cells [1, 10, 20, 68]. Indeed, this is demonstrated herein for c-Myc and p53, which are regulated by iron levels and act antagonistically to affect the expression of key polyamine pathway proteins (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…These metabolic differences are modulated by the different molecular phenotypes frequently observed in cancer cells [1, 10, 20, 68]. Indeed, this is demonstrated herein for c-Myc and p53, which are regulated by iron levels and act antagonistically to affect the expression of key polyamine pathway proteins (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…ODC is a direct target of the transcription factor Myc and is required for Myc-induced lymphoma development 5 . Research investigating the role of ODC and ODC-associated proteins as oncogenic factors in neuroblastoma (NB), a pediatric malignancy that arises in neural crest-derived cells of the sympathetic nervous system, has gained significant momentum 6; 7; 8; 9; 10; 11; 12; 13; 14; 15; 16; 17 . Evidence exists that ODC is a direct transcriptional target of the Myc-related MYCN transcription factor 18; 19 , and it is therefore not surprising that the role of ODC and ODC-associated proteins is especially clear in the aggressive NB tumors that show amplification of the MYCN gene 20; 21; 22 .…”
Section: Introductionmentioning
confidence: 99%
“…AMD1 , located on chromosome 6, encodes the S-adenosylmethionine decarboxylase 1, an enzyme that catalyzes the conversion of S-adenosyl methionine to S-adenosylmethioninamine, controlling the second rate-limiting step in the polyamine biosynthetic pathway 42 . Polyamines are highly regulated essential cations that are elevated in rapidly proliferating tissues of diverse cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are highly regulated essential cations that are elevated in rapidly proliferating tissues of diverse cancers. Reduced levels of intracellular polyamines activate checkpoints that constrain proliferation, as seen in senescent and post-mitotic cells, while enhanced polyamine synthesis accompanies oncogenic proliferation 42, 43 . Recent studies demonstrated that rapamycin complex 1 (mTORC1)-dependent AMD1 upregulation sustains polyamine metabolism in prostate cancer 44 .…”
Section: Discussionmentioning
confidence: 99%